In & out of the learning community: a phenomenological study of the learning community experience of adult learners - Jackowski, Barbara, author; Banning, James, advisor; Davies, Timothy Gray, advisor (Colorado State University. Libraries, 2009)
This qualitative study explored the lived experience of adult learners who had participated in a learning community. The phenomenon was examined through data collected by interviews with five students who had completed Associate of Art degrees through a learning community and then continued the upper division work towards a Bachelor of Arts in a more traditional setting. The structures of connection, support, and sentiments provided the framework for the meaning and essence of the phenomenon. Connection describes the relational experience of the participants in and out of the learning community. The participants experienced connection in student-to-student, student-to-faculty, and student-to-institution relationships. The structure of support described the means and methods used in and out of the learning community to address the obstacles that threatened the success of the adult learners. The need for systemic support, academic support, and emotional support was shared by the participants. The third structure of sentiments emerged from the attitudes, thoughts, and judgments the participants had for their learning community and more traditional experience. Considered together these structures frame the essence of their experience, a subtle shift. As a result of exposure to a learning community, as the participants transitioned into the more traditional educational setting they experienced a small but important shift in attitude or behavior reflecting their new situations. Each participant experienced a subtle shift as they proceeded from the learning community into the more traditional environment. Each experienced a shift in how they perceived themselves as students, a shift that redefined their meaning of the roles and responsibilities of the system and their participation with that system.
In and out of the learning community: a phenomenological study of the learning community experience of adult learners
Keywords: adult learners; associate degree; learning community; community college education; adult education; phenomenology